A Survey on Non-English Department Students’ Motivation and Attitude Toward English Language Learning - Asmiati, Asmiati; Permana, Dio Resta; Angraini, Nike (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The low English proficiency level that faced by Indonesia is the problem highlighted in English First’s survey in 2023. This research is aimed at determining which factors influence students' motivation and learning attitudes toward English language learning, to generalize the motivation and attitude possessed by students in Palembang. This study used a cross-sectional survey design on non-English department students at four universities in Palembang, Indonesia. 427 participants were involved in this research from four sample universities in the population. The data was collected through quantitative method and using two distribution methods by online and offline. The data were presented in graphical form compared the mean value of motivational factors and attitudinal tendencies in English learning. The correlation test results between motivation and students' attitudes towards English learning showed a strong correlation. Several motivational interpretations lead to the conclusion that, according to this research, students had a higher predisposition to learn English integratively and had a positive attitude with a higher cognitive aspect tendency. The findings of this study are likely to assist numerous interested parties in improving and maintaining student learning achievement in English language learning